2020
DOI: 10.1021/acsami.0c01528
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Bone-Mimicking High-Performance Structured Poly(lactic acid) by an Elongational Flow Field and Facile Annealing Process

Abstract: Poly(lactic acid) (PLA) as one of the most promising biodegradable polymers is being tremendously restricted in large-scale applications by the notorious toughness, ductility, and heat distortion resistance. Manufacturing PLA with excellent toughness, considerable ductility, balanced strength, and great heat distortion resistance simultaneously is still a great challenge. Natural structural materials usually possess excellent strength and toughness by elaborately constructed sophisticated hierarchical architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 40 publications
0
38
0
1
Order By: Relevance
“…Initially, the strong tensile stress stemming from the compression effect of convergence flow path forces large aggregated OMMT layers to separate to stacks of silicate tactoids. In the meanwhile, the tensile stress also facilitates the disentanglement and the orientation of PVDF chains, which are more conducive to the diffusion of chains 20,29 . PVDF chains and OMMT tactoids accumulate large amounts of energy in the compression process of convergence region, which is converted into the strong motion energy of molecular chains and OMMT in the form of the tensile stress when entering the divergent region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the strong tensile stress stemming from the compression effect of convergence flow path forces large aggregated OMMT layers to separate to stacks of silicate tactoids. In the meanwhile, the tensile stress also facilitates the disentanglement and the orientation of PVDF chains, which are more conducive to the diffusion of chains 20,29 . PVDF chains and OMMT tactoids accumulate large amounts of energy in the compression process of convergence region, which is converted into the strong motion energy of molecular chains and OMMT in the form of the tensile stress when entering the divergent region.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the plasticizing equipment based on elongational flow field has been gradually applied to the processing of high viscosity polymers, such as, ultrahigh molecular weight polyethylene (UHMWPE), 18 binary‐phase incompatible polymers 19,20 and nano‐paricle or nano‐fiber based composites 21,22 . Some researchers established theoretical models for the influence of processing flow field on mixing dispersion in the compounding process of polymer nanocomposites 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Poly-L-lactic acid (PLA) as a biodegradable and biocompatible polymer, has attracted intensive attentions of researchers. Simple and effective methods to improve the crystallization of the PLA matrix for further mechanical-strength enhancements were proposed [ 43 , 44 , 45 , 46 ].…”
Section: Applications Of Elongational Flow Dominated Plasticizing and Convey Devicesmentioning
confidence: 99%
“…With an optimized TPU content of 25 wt%, an impact strength of 73.5 kJ m −2 was achieved. Further study demonstrated that the interfacial relaxation through the plastic deformation of PLA/TPU matrix endowed a better absorption and dissipation of fracture energy after an annealing process [ 45 ]. Thus, reaching a balanced toughness of 90.3 kJ m −2 and a stiffness of ~2.15 GPa.…”
Section: Applications Of Elongational Flow Dominated Plasticizing and Convey Devicesmentioning
confidence: 99%
See 1 more Smart Citation